An Ultraviolet Halitosis Detection Using An Open-Path Optical Fibre Based Sensor - Suzalina, Kamaruddin; Hadi, Manap (IJEI Journal, 2018)
This paper provides an overview of the development of the optical fibre based sensor to detect halitosis (bad breath) using an open-path technique. The unique characteristic of each compound which corresponds to their identification allows the open-path technique to be best suited method in measuring gaseous compounds. In this study, the technique is designed to analyze the absorption spectral lines of Methyl Mercaptan gas within the ultraviolet wavelength region. Then, the developed sensor was used in cross sensitivity evaluation between Methyl Mercaptan and other breathing gases such as Oxygen, Carbon Dioxide, and water vapor to confirm the reliability of the sensor. The absorption cross section spectrum of the Methyl Mercaptan which generated from the study almost match up the theory with the potential peak selection at 203.5nm. The cross sensitivity analysis carried out shows that there are no distinctive interference effects within the wavelength region of 200 nm to 250 nm especially at 203.5 nm absorption peak. Experimental results validate the use of the open-path fibre technique in a halitosis sensor within the selected ultraviolet region.